Glycosaminoglycans of arterial basement membrane-like material from cultured rabbit aortic myomedial cells - Heickendorff, L; Ledet, T (Biochimica et biophysica acta, 1984)
Arterial basement membrane-like material was prepared by a sonication-differential centrifugation technique from cultures of rabbit aortic myomedial cells after metabolic labelling with [35S]sulphate and [3H]glucosamine. Labelled glycosaminoglycans were obtained from isolated basement membrane-like material by proteinase digestion and gel filtration. Glycosaminoglycans were identified by a combination of Sephadex G-50 chromatography and sequential degradation with nitrous acid, Streptomyces hyaluronidase, testicular hyaluronidase and chondroitinase ABC. The data showed that heparan sulphate and chondroitin sulphate were the predominant glycosaminoglycans of myomedial basement membrane-like material. Heparan sulphate accounted for about 55% of [3H]glucosamine-labelled glycosaminoglycans. In addition small amounts of hyaluronic acid was present. Only trace amounts of dermatan sulphate was found. The glycosaminoglycans were analysed by DEAE-cellulose chromatography. Two major peaks were found in the chromatogram consistent with the predominance of heparan sulphate and chondroitin sulphate.